Relationship Between Rotational Device Kinematics and Head Kinematics in a Large Animal Model of Traumatic Brain Injury - Declan A. Patton; Ciara S. Grunig; Jessica R. McQuaid; Andrew B. Dodd; Mandy K. Pacheco; Josef M. Ling; Tracey V. Wick; Divyasree Sasi Kumar; Vadim Zotev; Rachel E. Kinsler; Kristy B. Arbogast; Andrew R. Mayer (Annals of Biomedical Engineering, 2025)

Head Impact Kinematics and Brain Tissue Strains in High School Lacrosse - Declan A. Patton; Colin M. Huber; Divya Jain; Svein Kleiven; Zhou Zhou; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2024)

Consensus Head Acceleration Measurement Practices (CHAMP): Laboratory Validation of Wearable Head Kinematic Devices - Lee Gabler; Declan Patton; Mark Begonia; Ray Daniel; Ahmad Rezaei; Colin Huber; Gunter Siegmund; Tyler Rooks; Lyndia Wu (Annals of Biomedical Engineering, 2022)
Wearable devices are increasingly used to measure real-world head impacts and study brain injury mechanisms. These devices must undergo validation testing to ensure they provide reliable and accurate information for head impact sensing, and controlled laboratory testing should be the first step of validation. Past validation studies have applied varying methodologies, and some devices have been deployed for on-field use without validation. This paper presents best practices recommendations for validating wearable head kinematic devices in the laboratory, with the goal of standardizing validation test methods and data reporting. Key considerations, recommended approaches, and specific considerations were developed for four main aspects of laboratory validation, including surrogate selection, test conditions, data collection, and data analysis. Recommendations were generated by a group with expertise in head kinematic sensing and laboratory validation methods and reviewed by a larger group to achieve consensus on best practices. We recommend that these best practices are followed by manufacturers, users, and reviewers to conduct and/or review laboratory validation of wearable devices, which is a minimum initial step prior to on-field validation and deployment. We anticipate that the best practices recommendations will lead to more rigorous validation of wearable head kinematic devices and higher accuracy in head impact data, which can subsequently advance brain injury research and management.

On-Field Deployment and Validation for Wearable Devices - Calvin Kuo; Declan Patton; Tyler Rooks; Gregory Tierney; Andrew McIntosh; Robert Lynall; Amanda Esquivel; Ray Daniel; Thomas Kaminski; Jason Mihalik; Nate Dau; Jillian Urban (Annals of Biomedical Engineering, 2022)
Wearable sensors are an important tool in the study of head acceleration events and head impact injuries in sporting and military activities. Recent advances in sensor technology have improved our understanding of head kinematics during on-field activities; however, proper utilization and interpretation of data from wearable devices requires careful implementation of best practices. The objective of this paper is to summarize minimum requirements and best practices for on-field deployment of wearable devices for the measurement of head acceleration events in vivo to ensure data evaluated are representative of real events and limitations are accurately defined. Best practices covered in this document include the definition of a verified head acceleration event, data windowing, video verification, advanced post-processing techniques, and on-field logistics, as determined through review of the literature and expert opinion. Careful use of best practices, with accurate acknowledgement of limitations, will allow research teams to ensure data evaluated is representative of real events, will improve the robustness of head acceleration event exposure studies, and generally improve the quality and validity of research into head impact injuries.

Non-Linear Device Head Coupling and Temporal Delays in Large Animal Acceleration Models of Traumatic Brain Injury - Andrew R. Mayer; Josef M. Ling; Declan A. Patton; David D. Stephenson; Andrew B. Dodd; Rebecca J. Dodd; Julie G. Rannou-Latella; Douglas H. Smith; Victoria E. Johnson; D. Kacy Cullen; Timothy B. Meier; Rachel E. Kinsler (Annals of Biomedical Engineering, 2022)
Accurate characterization of head kinematics following an external blow represents a fundamental aspect of traumatic brain injury (TBI) research. The majority of previous large animal studies have assumed an equivalent relationship between the device delivering the impulsive load and subsequent head kinematics rather than performing direct measurement (sensors or videography). The current study therefore examined factors affecting device/head coupling kinematics in an acceleration TBI model. Experiment 1 indicated ~ 50% reduction in peak angular velocity for swine head relative to the device, with an approximate doubling in temporal duration. The peak angular velocity for the head was not significantly altered by variations in restraint device (straps vs. cables), animal positioning or body mass. In Experiment 2, reducing the impulsive load by 32% resulted in only a 14% reduction in angular velocity of the head (approximately 69% head/device coupling ratio), with more pronounced differences qualitatively observed for angular momentum. A temporal delay was identified in initial device/head coupling, potentially a result of soft tissue deformation. Finally, similar head kinematics were obtained regardless of mounting the sensor directly to the skull or through the scalp (Experiment 3). Current findings highlight the importance of direct measurement of head kinematics for future studies.

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)